The Influence of the Instagram Account @TUBABAARTFESTIVAL on the Brand Awareness of Tubaba Art Festival - Muhammad Hafizh Westtian; Hanindyalaila Pienrasmi; M. Denu Poyo (International Journal of Education, Vocational and Social Science, 2025)
This study aims to analyze whether the Instagram account @tubabaartfestival influences the enhancement of brand awareness for the Tubaba Art Festival in West Tulang Bawang. Brand awareness is a critical factor in attracting public attention to art events. The research employs a quantitative approach with 100 respondents drawn from the account’s followers. Data were collected via a closed ended questionnaire designed to measure respondents’ perceptions and knowledge of the festival. SPSS 25 was used to analyze the data and test the significance of the influence. The findings show that the @tubabaartfestival account has a positive and significant effect on increasing brand awareness of the Tubaba Art Festival. A simple linear regression yielded a significance value of 0.000 (<0.05) and a coefficient of determination of 0.865, indicating that 86.5% of the variance in brand awareness can be explained by the Instagram account. Consequently, the study concludes that social media, particularly Instagram, plays a vital role in building brand awareness for events and can serve as an effective promotional strategy for future arts and cultural activities.